1975
DOI: 10.1111/j.1432-1033.1975.tb04006.x
|View full text |Cite
|
Sign up to set email alerts
|

Molecular Morphology of Ribosomes

Abstract: Using either soluble or solid-state lactoperoxidase, a comparison was made between the enzymic iodination of ribosomal proteins iodinated as 3 0 4 and 50-S subunits or as 7 0 4 monosomes. Proteins S7, S11 and S12 of the 30-S subunit and proteins L2, L11, L26 and L28 of the 50-S subunit were labelled to a greater extent in isolated particles than in the 70-S ribosome. In contrast, proteins S4, S6, S19 and S20 were labelled to a lesser extent in the isolated subunit. No significant differences were observed in t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
5
2

Year Published

1975
1975
1985
1985

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(8 citation statements)
references
References 14 publications
1
5
2
Order By: Relevance
“…In spite of this difference, the distribution of 125 1 among the ribosomal proteins (table 1) was reproducible in 7 different experiments performed with 2 independent preparations of ribosomes. However, it differs from iodination patterns reported [9,10,16], probably due to our different experimental conditions. Streptomycin and viomycin did not appreciably affect the total incorporation of 125 I by 70 S ribosomes (not shown).…”
Section: Resultscontrasting
confidence: 50%
“…In spite of this difference, the distribution of 125 1 among the ribosomal proteins (table 1) was reproducible in 7 different experiments performed with 2 independent preparations of ribosomes. However, it differs from iodination patterns reported [9,10,16], probably due to our different experimental conditions. Streptomycin and viomycin did not appreciably affect the total incorporation of 125 I by 70 S ribosomes (not shown).…”
Section: Resultscontrasting
confidence: 50%
“…P and T correspond to the puromycin and thiostrepton binding sites, respectively [see Wittmann (1983)], oleophilic reagents, make us fairly confident of the specificity of SI8 labeling. Another point in favor of this specificity is the fact that SI8 is considerably less labeled in the 70S ribosome than in the small subunit, since the labeling of SI8 by unspecific reagents does not seem to be affected by subunit association (Michalski & Sells, 1975).…”
Section: Discussionmentioning
confidence: 99%
“…It has been reported that upon formation of the 70S ribosome a conformational change of the subparticles can take place (see, e.g. Michalski and Sells, 1975 ;Litman et al, 1974;Chang, 1973 ;etc.). However, in our opinion it seems unlikely that this conformational change could significantly influence the effectivity of subparticle labelling because we used a chemically non-specific reagent.…”
Section: H Specificity Of the Sin-analog Photoreaction With Ribosomamentioning
confidence: 99%